2004
DOI: 10.2320/matertrans.45.1915
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Copper and Zinc Ions by Hollow Fiber Supported Liquid Membrane Containing LIX84 and PC-88A

Abstract: The separation of Cu 2þ and Zn 2þ in mixed solutions of zinc and copper sulfate has been studied using hollow fiber supported liquid membrane (HFSLM). The extractants for Cu 2þ and Zn 2þ were LIX84(anti-2-hydroxy-5-nonyl acetophenoneoxime) and PC-88A(2-ethylhexylphosphonic acid mono-2 ethylhexyl ester) which were diluted in kerosene, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The Cyanex 272 has molecular weight of 290, a Brookfield viscosity of 142 × 10 −3 Pa s (142 cP) at 25 • C, density of 0.92 g/cm 3 at 24 • C, and a purity of 85%. The active component C 16 Kerosene (bp 180-270 • C) and tri-n-butyl-phosphate (TBP) supplied by Junsei Chemicals Co., Ltd., Japan were used as a diluent and phase modifier, respectively, for all sets of experiments.…”
Section: Chemicals/reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cyanex 272 has molecular weight of 290, a Brookfield viscosity of 142 × 10 −3 Pa s (142 cP) at 25 • C, density of 0.92 g/cm 3 at 24 • C, and a purity of 85%. The active component C 16 Kerosene (bp 180-270 • C) and tri-n-butyl-phosphate (TBP) supplied by Junsei Chemicals Co., Ltd., Japan were used as a diluent and phase modifier, respectively, for all sets of experiments.…”
Section: Chemicals/reagentsmentioning
confidence: 99%
“…The separation processes like Co-Ni [10][11][12][13], Co-Zn [14], and Co-Mn [15] have also been investigated by SLM technique. Several extractants such as D2EHPA [6][7][8]14,15], PC88A [15], LIX84 [16], and Cyanex 921 [17], etc. have been used for the extraction and separation of metals.…”
Section: Introductionmentioning
confidence: 99%
“…As with solvent extraction, selective recovery of metal ions can be achieved through use of suitable extractant and manipulating chemistry of feed and stripping phases [ 7 , 8 , 10 ]. In many SLM studies, which involved recovering copper, chelating oxime extractants were found to transport copper preferably over other metal ions [ 11 , 12 , 13 ], whereas solvating extractants such as Cyanex 923 were succesful in transporting metals that assumed metal-salt forms in aqueous feed [ 14 , 15 ]. Some studies employed ionic liquids with tailorable chemical structure to facilitate transport of target metal ions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al investigated the separation of zinc and copper by hollow fiber supported liquid membrane containing LIX 84 and PC-88A as mobile carriers. The influence of numerous operational factors on separation and permeation rate of Zn (II) and Cu (II) has been studied [25].…”
Section: Introductionmentioning
confidence: 99%